Pentingnya pendidikan Karakter dalam dunia pendidikan - Fatalaiha, Sheylamita Amanah (Maliki Interdisciplinary Journal, 2024)
Character of education: It is absolutely necessary in the social environment, both at home and in the classroom. Event now this is by and by not a part character of tutoring youth through adolescence yet furthermore adults. Absolutely basic for the perseverance of this country. Competition imagine what will emerge sooner rather than later. Obviusly it would be our weight and parent until further notice. Around then, the children will face challenge with accomplices from various countries all around the planet. In fact, we are currently entering the work year and will share similar feelings. Demand the idea of HR in the coming thousand years irrefutably requires extraordinary individual. Nevertheless, the individual is the fundamental individual goal.